Enhanced remediation of fracturing flowback fluids by the combined application of a bioflocculant/biosurfactant-producing Bacillus sp. SS15 and its metabolites. (September 2022) - Zeng, Feng; Zhou, Hanghai; Lin, Xiaoyun; Li, Yanhong; Liang, Yanpeng; Xie, Qinglin; Atakpa, Edidiong Okokon; Shen, Chaofeng; Zhang, Chunfang
Abstract: Fracturing flowback fluids (FFFs), which is generated from the process of oil and gas exploitation, is one of the major environmental concerns. In this study, a bacterial strain, Bacillus sp. SS15, capable of producing both bioflocculant (BF) and biosurfactant (BS), was isolated from oil-contaminated mudflat sediment. The BS produced by SS15 was identified as lipopeptide, which could reduce the surface tension of water from 74.2 mN/m to 36.6 mN/m with a critical micelle concentration of 44.4 mg/L. It also exhibited strong tolerance against a wide range of pH (2–12), temperature (4–60 °C), and salinity (0–100 g/L). Meanwhile, the BF produced by SS15 exhibited high flocculating activity (84.9%) for kaolin suspension, and was confirmed to be thermostable, salt-tolerant, and alkaliphilic. The combined treatment of bioremediation (introducing SS15 and BS) followed by flocculation (introducing BF) greatly promoted the removal of chroma (85.7% reduction), suspended solids (94.4% reduction), chemical oxygen demand (84.9% reduction), n -alkanes (50.0% reduction), and polycyclic aromatic hydrocarbons (66.5% reduction), respectively. The genome analysis showed that strain SS15 possessed abundant genes related to the synthesis of carbohydrate, protein, and lipid, which might play an important role in BF and BS synthesis. The findings in this study demonstrated that Bacillus sp. SS15 has promising prospect in the remediation of FFFs. Graphical abstract: Image 1 Highlights: Bacillus sp. SS15 is capable of producing both bioflocculant and biosurfactant. Both bioflocculant and biosurfactant showed excellent activity and stability. Bioflocculant and biosurfactant were employed in treating fracturing flowback fluids. 86% of chroma, 94% of SS, 85% of COD, and more than 50% of hydrocarbons were removed. SS15 genome contains abundant genes related to BF/BS synthesis.